Screening Sebagai Upaya Perlindungan Hukum Bagi Investor Saham Syariah di Indonesia - Abdul Hafiz; Abdul Mujib (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
One of the interesting things in Islamic stocks is the existence of a screening system that indirectly shows the cautious attitude of the authorities and institutions that oversee the performance of Islamic stocks in the capital market. This screening is carried out to ensure that Islamic stocks remain on the right track. The screening process is carried out twice a year aimed at ensuring that stocks that have entered the sharia category continue to perform in accordance with sharia principles or have gone out of the sharia channel. The method used in this study is a qualitative research method using a descriptive qualitative approach. Shares that are no longer sharia from DES can no longer be transacted. Legal protection provided by OJK as the capital market regulator in Indonesia is by providing two options to investors: First: Immediately sell the shares owned to the issuer that issued the shares as stated in POJK no. 17 / POJK.04 / 2015. Second: If the investor does not want to sell the shares, then the investor can open a new account for conventional shares in order to transact again with the shares. This option is not mentioned in POJK no. 17/POJK.04/2015, but OJK still provides legal protection in the form of a way out so that the shares owned can be transacted in conventional stock accounts so that investors do not experience losses.